PENGUKURAN WAKTU STANDAR PROSES KERJA MESIN BANDSAW DAN CROSS CUT UNTUK PERENCANAAN DAN EVALUASI PEMENUHAN - Nanta Sigit; Fahrur Rozi; Ardinda, Larasati Purna; Rahmat Afandi (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
Standard time measurement of bandsaw and cross-cut machine work processes for planning and evaluating order fulfillment] The furniture industry is continuously innovating to produce the best products, with buyers' preferences related to function, quality, and design. To increase productivity, companies need to optimize machine cycle times and reformulate production time durations. Lead time needs to be optimized to ensure order fulfillment until the transaction is completed on time. In measuring productivity, standard time is critical to setting production targets, budgets, product cost estimates, and machine requirements, and determining standard operator wages to measure. Companies in the garden furniture sector need to calculate standard time in their production processes, particularly in the RST (Raw Sawn Timber) processing stage, in order to achieve on time production targets and avoid potential losses. Productivity analysis of the RST processing stage is carried out by calculating the standard time of the bandsaw and cross-cut or radial arm saw machines. The research was conducted through the motion study measurement, uniformity and sufficiency testing of data, and normal and standard time calculations to determine the required duration for each production stage. The time study measurement results and standard time calculations for 18 work elements show that the standard time in the RST processing stage is 4.92 minutes or equivalent to 12 units/hour, which means the company can ideally produce 88 unit of products per day